ADAPTIVE GOVERNANCE DALAM PENGELOLAAN OBJEK WISATA TAMAN ALAM MAYANG DI PEKANBARU PADA MASA PANDEMI COVID-19 - Endang Agustin; Hasim As’ari (Cross-border, 2022)
The decline in the number of visits to the Alam Mayang Park Tourism Object in Pekanbaru has decreased significantly. The emergence of the Covid-19 Virus urges stakeholders to be adaptive. This condition is called Adaptive Governance. Adaptive governance is governance that aims to increase adaptive capacity in order to overcome and reduce disaster risk and vulnerability. The purpose of this study is to analyze Adaptive Governance in the management of the Mayang Natural Park Tourism Object in Pekanbaru During the Covid-19 Pandemic and identify barriers to Adaptive Governance in the management of the Mayang Natural Park Tourism Object in Pekanbaru During the Covid-19 Pandemic. This study uses a qualitative method where the data collection techniques used are interviews, observation and documentation. This study uses the theory according to Hulbert (2016). Data analysis techniques in this study are data reduction, data presentation and conclusion drawing. The results of this study indicate that the management of the Alam Mayang park tourism object in Pekanbaru City has not been adaptive. The inhibiting factors in this study were lack of alertness, lack of supervision, not running health programs (prokes), and lack of awareness of visitors.